Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
First, let’s start by evaluating the given mathematical problem: [tex]\( y = \sqrt{\sin x - \cos x} \)[/tex] with [tex]\( x = 45^\circ \)[/tex].
Step 1: Convert the angle to radians.
Since trigonometric functions in mathematics often use radians, we'll convert [tex]\( 45^\circ \)[/tex] to radians. The conversion from degrees to radians is done using the formula:
[tex]\[ \theta_{radians} = \theta_{degrees} \times \frac{\pi}{180} \][/tex]
For [tex]\( x = 45^\circ \)[/tex]:
[tex]\[ x = 45^\circ \times \frac{\pi}{180} = \frac{\pi}{4} \][/tex]
Step 2: Calculate [tex]\(\sin x\)[/tex] and [tex]\(\cos x\)[/tex] for [tex]\( x = \frac{\pi}{4} \)[/tex].
We know that:
[tex]\[ \sin \left( \frac{\pi}{4} \right) = \frac{\sqrt{2}}{2} \][/tex]
[tex]\[ \cos \left( \frac{\pi}{4} \right) = \frac{\sqrt{2}}{2} \][/tex]
Step 3: Substitute [tex]\(\sin x\)[/tex] and [tex]\(\cos x\)[/tex] into the expression [tex]\(\sin x - \cos x\)[/tex].
[tex]\[ \sin \left( \frac{\pi}{4} \right) - \cos \left( \frac{\pi}{4} \right) = \frac{\sqrt{2}}{2} - \frac{\sqrt{2}}{2} = 0 \][/tex]
Step 4: Calculate the value of [tex]\( y \)[/tex].
[tex]\[ y = \sqrt{\sin x - \cos x} = \sqrt{0} = 0 \][/tex]
Conclusion:
For [tex]\( x = 45^\circ \)[/tex], the value of [tex]\( y \)[/tex] is [tex]\( y = 0 \)[/tex]. The provided angle [tex]\( y = 90^\circ \)[/tex] does not alter the evaluation of the expression since it's only involved in the problem statement to check the result of [tex]\( y = 0 \)[/tex]. Hence, the solution has been evaluated correctly without the angle [tex]\( y \)[/tex].
Thus, the final value is:
[tex]\[ y = 0 \][/tex]
Step 1: Convert the angle to radians.
Since trigonometric functions in mathematics often use radians, we'll convert [tex]\( 45^\circ \)[/tex] to radians. The conversion from degrees to radians is done using the formula:
[tex]\[ \theta_{radians} = \theta_{degrees} \times \frac{\pi}{180} \][/tex]
For [tex]\( x = 45^\circ \)[/tex]:
[tex]\[ x = 45^\circ \times \frac{\pi}{180} = \frac{\pi}{4} \][/tex]
Step 2: Calculate [tex]\(\sin x\)[/tex] and [tex]\(\cos x\)[/tex] for [tex]\( x = \frac{\pi}{4} \)[/tex].
We know that:
[tex]\[ \sin \left( \frac{\pi}{4} \right) = \frac{\sqrt{2}}{2} \][/tex]
[tex]\[ \cos \left( \frac{\pi}{4} \right) = \frac{\sqrt{2}}{2} \][/tex]
Step 3: Substitute [tex]\(\sin x\)[/tex] and [tex]\(\cos x\)[/tex] into the expression [tex]\(\sin x - \cos x\)[/tex].
[tex]\[ \sin \left( \frac{\pi}{4} \right) - \cos \left( \frac{\pi}{4} \right) = \frac{\sqrt{2}}{2} - \frac{\sqrt{2}}{2} = 0 \][/tex]
Step 4: Calculate the value of [tex]\( y \)[/tex].
[tex]\[ y = \sqrt{\sin x - \cos x} = \sqrt{0} = 0 \][/tex]
Conclusion:
For [tex]\( x = 45^\circ \)[/tex], the value of [tex]\( y \)[/tex] is [tex]\( y = 0 \)[/tex]. The provided angle [tex]\( y = 90^\circ \)[/tex] does not alter the evaluation of the expression since it's only involved in the problem statement to check the result of [tex]\( y = 0 \)[/tex]. Hence, the solution has been evaluated correctly without the angle [tex]\( y \)[/tex].
Thus, the final value is:
[tex]\[ y = 0 \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.